2023
DOI: 10.1002/solr.202201078
|View full text |Cite
|
Sign up to set email alerts
|

High‐Temperature Equilibrium of 3D and 2D Chalcogenide Perovskites

Abstract: Chalcogenide perovskites have been recently proposed as novel absorber materials for photovoltaic applications. BaZrS3, the most investigated compound of this family, shows a high absorption coefficient, a bandgap of around 1.8 eV, and excellent stability. In addition to the 3D perovskite BaZrS3, the Ba–Zr–S compositional space contains various 2D Ruddlesden–Popper phases Ban + 1ZrnS3n + 1 (with n = 1, 2, 3) which have recently been reported. Herein, it is shown that at high temperature the Gibbs free energies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The results suggest that chalcogenide perovskite compounds may need to master the equilibrium of the two-phase structure at low temperatures, and finally be deposited and integrated into optoelectronic devices. 10 Ramanandan et al further investigated the thermodynamic distribution and study of BaZrO 3 (precursor) vulcanized by H 2 S. As the temperature rises, the overall structure is completely vulcanized at 1000 1C. The sensitivity of BaZrS to temperature was discussed.…”
Section: Energy and Environmental Science Perspectivementioning
confidence: 99%
See 3 more Smart Citations
“…The results suggest that chalcogenide perovskite compounds may need to master the equilibrium of the two-phase structure at low temperatures, and finally be deposited and integrated into optoelectronic devices. 10 Ramanandan et al further investigated the thermodynamic distribution and study of BaZrO 3 (precursor) vulcanized by H 2 S. As the temperature rises, the overall structure is completely vulcanized at 1000 1C. The sensitivity of BaZrS to temperature was discussed.…”
Section: Energy and Environmental Science Perspectivementioning
confidence: 99%
“…It can be seen that most of the chalcogenide solar cells prepared in these experiments are synthesized by solid-state reaction. 10 A common processing method is to seal the element or binary chalcogenide precursors in ampoules and heat them at high temperatures for hours or days. This classical processing and growth method often requires a temperature of more than 1000 °C and a reaction cycle of several hours or even days, so that the reaction material can be completely diffused on a micron basis, to obtain a uniform crystalline material (Table 1).…”
Section: Chalcogenide Inorganic Thin Film Solar Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, their preparation in high purity shows a sensitive dependence with the reaction conditions. 17 Their synthetic preparation has predominantly involved the reaction of elemental or binary-chalcogenide reactants heated to 1200 °C inside sealed, evacuated quartz ampules. Recent studies have also demonstrated that lowertemperature reactions involving the use of sulfurization agents, e.g., boron sulfides or elemental sulfur, can also be effective in reactions with ternary oxides or other precursors.…”
Section: Introductionmentioning
confidence: 99%